Efectividad de un programa educativo en el conocimiento sobre autocuidado en adultos con diabetes mellitus - Cabanillas Cabanillas, Estefanny Giovanna (2017)
The present research is quantitative, pre-experimental, cross-sectional, was carried out during the year 2016, in order to determine the effectiveness of the educational program "Promoting my care" in self-care knowledge in adults with diabetes mellitus, Support Hospital Chepén. The subjects of investigation were 80 patients, who were given a pre and post test. The results obtained are as follows: Before applying the educational program, 1.2% had poor knowledge level, 50.0% regular knowledge level and 48.8% good knowledge level. After applying the educational program, 100% of adults presented good knowledge. 90.0% of adults have improved their level of knowledge about self-care, so the educational program is effective. T student of -12,557 with probability 0.000 being highly significant